2021
DOI: 10.1111/socf.12689
|View full text |Cite
|
Sign up to set email alerts
|

Black Ballerinas: The Management of Emotional and Aesthetic Labor*

Abstract: Ballet is an elite and predominantly white profession that has mirrored history. Black dancers have been historically excluded and remain severely underrepresented through controlling images, discrimination, and marginalization. As an occupation, ballet demands intensive emotional and aesthetic labor. This research relies on interviews to better understand the experiences of Black women in ballet in context. It specifically examines the ways that Black dancers negotiate two forms of labor that have typically b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
(58 reference statements)
0
8
0
5
Order By: Relevance
“…The idea of the docile body that is shaped or molded for aesthetic and profit reasons has been explored in other gendered sectors such as ballet ( Green, 2002 ). A fashion model’s overall “look” and sexuality is controlled by agents, bookers, designers, and stylists ( Holla, 2016 ), thus, the sense of embodiment described in studies of dancers ( Green, 2002 ; Robinson, 2021 ) was absent from our study. Models are also so-called because they set the mode or fashion, not just for clothes but for body shapes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The idea of the docile body that is shaped or molded for aesthetic and profit reasons has been explored in other gendered sectors such as ballet ( Green, 2002 ). A fashion model’s overall “look” and sexuality is controlled by agents, bookers, designers, and stylists ( Holla, 2016 ), thus, the sense of embodiment described in studies of dancers ( Green, 2002 ; Robinson, 2021 ) was absent from our study. Models are also so-called because they set the mode or fashion, not just for clothes but for body shapes.…”
Section: Discussionmentioning
confidence: 96%
“…The youthful slender body remains virtually mandatory in high-profit, high-end modeling ( Holla, 2016 ). In addition to the physiological consequences of a low body mass, this pre-pubescent look has served to exclude black girls and women from aesthetic professions such as modeling and ballet ( Robinson, 2021 ). The idiom, “feeling like a piece of meat” has carnal connotations; in urban slang, it implies, “reducing a woman down to her sexual parts”( dictionary.com, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward to 2018, researcher Sekani Robinson presented quantitative research on Black women in American ballet companies in which she revealed that only 5% of the corps in major American companies was composed of Black dancers (Robinson, 2018). Despite some changes, such as the insertion of pointe shoes with a greater variety of skin colors that cater to non-white people, the representation in classical dance of Black men and women is still small, especially in leading roles.…”
Section: Two Artists: Representations Based On Josephine Baker and Me...mentioning
confidence: 99%
“…Avançando para 2018, a pesquisadora Sekani Robinson apresentou pesquisa quantitativa sobre mulheres negras nas companhias de balé norteamericanas na qual revelou que apenas 5% do corpo das grandes companhias norte-americanas era composto por bailarinas negras (Robinson, 2018). Apesar de algumas mudanças, como a inserção de sapatilhas de ponta com maior variedade de cores de pele, que atendam a pessoas não brancas, a representação na dança clássica de homens e mulheres negros ainda é pequena, em especial em papéis de destaque.…”
Section: Duas Artistas: Representações a Partir De Josephine Baker E ...unclassified